Supposed to be rare cause of intestinal obstruction; abdominal cocoon: report of two cases - Serter, Asli; KOCAKOÇ, ERCAN; KOCAKOÇ, ERCAN; Cipe, Gokhan (My University, 2013)
Abdominal cocoon, or sclerosing encapsulating peritonitis, is supposed to be rare cause of intestinal obstruction. It is characterized by totally or partially encasement of small bowel with a thick, fibrotic, cocoon-like membrane. We think this entity is not rare as previously thought. We reported two case-s clinical and imaging findings which diagnosed abdominal cocoon by surgery to increase awareness of this diagnosis. (C) 2013 Elsevier Inc. All rights reserved.